2020
DOI: 10.32539/bsm.v4i4.157
|View full text |Cite
|
Sign up to set email alerts
|

Fiberoptic Endoscopic Examination of Swallowing (FEES) Evaluation in Post Stroke Patients

Abstract: Introduction. Complications caused by post-stroke dysphagia increase the morbidity and mortality of patients. Although it has a significant effect on the functional abilities and worsening of the patient's prognosis, post-stroke dysphagia is still under-noticed and often undiagnosed. The importance of knowing the incidence of post-stroke dysphagia, not only to determine its relationship to the pathology of the disease but also to determine treatment plans or follow-up interventions. This study aims to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the middle-aged population, gastroesophageal and immunologic causes of dysphagia manifest, whereas in the elderly population neurologic and oncologic causes are observed [30] . The current study showed increased percentage of oropharyngeal dysphagia in males than females and this can be due to the underling etiologies encountered in this study which are mostly related to stroke and neurological conditions that are more prevalent in males [31] . This result is not in agreement with Cho et al [32] who stated that dysphagia is more prevalent in women than men across all age groups.…”
Section: Discussionmentioning
confidence: 56%
“…In the middle-aged population, gastroesophageal and immunologic causes of dysphagia manifest, whereas in the elderly population neurologic and oncologic causes are observed [30] . The current study showed increased percentage of oropharyngeal dysphagia in males than females and this can be due to the underling etiologies encountered in this study which are mostly related to stroke and neurological conditions that are more prevalent in males [31] . This result is not in agreement with Cho et al [32] who stated that dysphagia is more prevalent in women than men across all age groups.…”
Section: Discussionmentioning
confidence: 56%